A Practical Guide to Causal Mediation Analysis: Illustration With a Comprehensive College Transition Program and Nonprogram Peer and Faculty Interactions - Chi, W. Edward; Huang, Sijia; Jeon, Minjeong; Park, Elizabeth S.; Melguizo, Tatiana; Kezar, Adrianna (Frontiers in Education, 2022)
Experimental and quasi-experimental designs have been increasingly employed in education. Mediation analysis has long been used to measure the role of mediators. Recently, causal mediation analysis has been proposed and provides a modern approach to evaluate potential causal roles of mediators. Compared with the conventional mediation analysis, this new approach has several advantages including evaluating necessary assumptions to establish a valid causal role of the mediator of interest. Despite these advantages and the availability of various software programs, causal mediation analysis is not employed frequently in educational research. In this paper, we review and compare conventional mediation analysis and causal mediation analysis and provide a step-by-step guide and sample code to researchers using the free R package mediation in order to promote the application of causal mediation analysis in education. To illustrate the new approach, we analyze data collected from a Comprehensive College Transition Program (CCTP).